Designing Quality Accounting Information Towards Global Business Development - Nungki Yartono; Asyari; Olivia Yolanda; Hery Krisnandi (CV ODIS, 2023)
The role of Management in making Strategic Information System designs according to the company's vision is an advantage that must always be improved by providing totality awareness of all stakeholders of the importance of sustainable Information Planning to respond to global challenges. Accounting Information is an output for companies in the financial sector that is influenced by business strategy and internal control. This study provides a critical analysis of how business strategy, internal control, and human resource professionalism affect accounting information. The linear regression analysis test is a measuring tool for whether the dependent variable is influenced by the three independent variables. The research uses quantitative statistical methods with SPSS version 21. The results of the hypothesis test explain that business strategy has a significant positive effect on the quality of accounting information. Internal control has a significant positive effect on the quality of accounting information and HR professionalism has a significant positive effect on the quality of accounting information.